The reinstatement of Rafflesia banaoana (Rafflesiaceae), and implications for assessing species diversity and conservation requirements of the world's largest flowers - Tobias, AB; Thorogood, CJ; Malabrigo Jr, PL (Magnolia Press, 2023)
The Southeast Asian genus Rafflesia (Rafflesiaceae) is famous for possessing the world's largest flowers. All species are rare or threatened, so understanding taxonomic diversity in the genus is crucial for informing effective conservation practice. Here we examine R. banaoana, a poorly known taxon from the remote montane rainforests of the Kalinga Province in the Philippines. This species has been treated as conspecific with R. leonardi, and overlooked in systematic studies. Using stable yet hitherto neglected features such as the stigmatic fascia surface, disk shape, process structure, annulus interior and exterior distinction, and ovary shape, we demonstrate that R. banaoana is morphologically as well as ecologically distinct from R. leonardi, and requires reinstatement at the specific rank. We present our findings in the broader context of complexity in the genus Rafflesia in the Philippines, now considered the center of diversity, with 15 species described to date. We highlight the taxonomically confused R. banaoana as a case for careful observation of previously unexamined morphological characters, as well as ecology, to avoid overlooking cryptic taxa or species complexes and to inform representative sampling in systematic treatments. Such an approach will be essential for enhancing our understanding of the diversity of this enigmatic yet poorly understood genus at a time of unprecedented anthropogenic change and species extinction. In light of our findings, we recommend a holistic approach to the conservation of Rafflesia in the Philippines.